A Framework of Socioeconomic Organisation: Redefining Original Institutional Economics Along Critical Realist Philosophical Lines - Paschalis Arvanitidis (European Regional Science Association (ERSA), 2006)
The paper develops a theoretical framework of socioeconomic organisation to enrich understanding of the complex interrelation between economy and institutional environment. To achieve this, key elements from both new and old institutional economics are combined and integrated under the philosophical platform of critical realism. Institutionalist research can be, and has been, informed by a range of philosophical positions and analytical standpoints. Critical realism, in turn, has certain advantages, over the other philosophical perspectives, in discussing the institutional organisation of urban socioeconomy. These mainly stem from its ontological arguments that allow the dissociation of institutional structure from human agency, and acknowledge the separate identity and causal powers of institutions without undermining their agent-dependent nature. This is important because it enables a neat identification and analysis of the institutional qualities, mechanisms, causal powers and relations that characterise the socioeconomic fabric. Moreover, the fact that the realist ontology is compatible with a variety of economic theories renders its fusion with institutionalism on the whole both valid and feasible. The paper starts delineating the philosophical tenets of critical realism, which provide the basis for the development of a stratified ontological framework discussing the institutional organisation of the urban socioeconomy. In particular, a three-layer, interlocked reality is identified describing the complexity, multidimensionality, and dynamic character of the socioeconomic world. It is argued that deeper tendencies, capacities, 'instincts' and qualities of the human essence (understood as 'creativity', 'emulation' and 'culture') condition the institutional environment (differentiated in economic, political, legal, and social terms), which in turn constitutes the terrain upon which organisational arrangements are manifested and socioeconomic events are actualised. In these terms, institutions are defined as ingrained regularities or established rules of human life that mould and determine agents' perception, expectations and behaviour, providing order, stability and certainty in social interaction and economic organisation. The paper closes summarising the epistemological and methodological position espoused to establish a generic analytical framework that can be used to investigate the institutional texture of the urban/regional socioeconomic environment.
Keywords: 330